ANALISIS IMPLEMENTASI PROYEK PERUBAHAN JANGKA MENENGAH ALUMNI PELATIHAN KEMEMIMPINAN TINGKAT IV TAHUN 2017 - Embung Megasari (Lembaga Administrasi Negara, 2020)
This study aims to explore the factors of the implementation of Midterm-term Change Project proposed by alumni of Leadership Development Program (Diklatpim) Level held in 2017 in the Riau Province. Data was collected using interview technique and review of related documents. The informants included three parties namely the alumni as the owner of the change project, the alumni superior as the mentor and organizer of the Training. The results showed, from the perspective of implementation, there were internal factors (low willingness, seriousness and motivation, as well as alumni communication with limited work teams) and external (unavailability of IT staff, lack of support for infrastructure and budget facilities, inequality of perception between participants and stakeholders to supporting data, as well as the lack of direct attention of superiors as mentors) which is the cause of the suboptimal implementation of medium-term change projects. This research contributes to efforts to improve the implementation of medium- term change projects through an understanding of the factors that cause the low level of implementation of the project term change in 2017 Riau Province Diklatpim IV alumni.Keywords: leadership development, change project, training evaluation, Riau.